Geemu On!: A Preliminary Study Of Indie And Doujin Game Development In Japan - Helland, Christopher (Gamevironments, 2018)
This paper is a brief summary of a preliminary exploration of certain aspects of independent video game development in Japan. Initial interviews were conducted with researchers and indie game developers over a two-week period in Tokyo. Independent game developers from Kamakura were also interviewed as part of the research. Initial fieldwork was geared primarily toward doujin level game development and distribution. My key research question focused upon the religious and spiritual dimensions of doujin games. However, after conducting interviews it became clear that developers did not consider the Western frame or classification of religion and spirituality in their development but rather incorporated aspects of tradition, culture and values within their work.